Prevalência da utilização de tecnologias leves pela equipe de enfermagem de um hospital estadual - Pabliane Matias Lordelo Marinho; Thialla Andrade Carvalho; Maria Cláudia Tavares de Mattos; Eliana Ofélia Llapa-Rodríguez; Maria Pontes de Aguiar Campos (Universidade Federal do Ceará, 2017)
Objective: to describe the prevalence of the use of light technologies by the nursing team of a state hospital. Methods: cross-sectional and observational study. The sample consisted of 19 Nurses and 67 Nursing Technicians. The data were collected through direct simple observation using a validated instrument. Chi-square was used to compare the use of light technologies between the nursing categories. Results: there was prevalence of nursing technicians, females, with no partner and with an employment relationship. In the "Bonding" dimension, the interventions presence and security enhancement prevailed for nursing technicians and nurses, respectively. In the "Welcoming" dimension, surveillance and security were the most used by both categories. Conclusion: evaluation of the prevalence of light technologies showed that the dimensions "Welcoming" and "Bonding" were the most used by the nursing team and that nurses use them more often than the Nursing Technicians in the studied unit.